2021
DOI: 10.3390/life11060483
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge of Long Non-Coding RNA HOTAIR in Breast Cancer Progression and Its Application

Abstract: Breast cancer is one of the most devastating cancers with high morbidity and mortality in females worldwide. Breast tumorigenesis and further development present great uncertainty and complexity, and efficient therapeutic approaches still lack. Accumulating evidence indicates HOX transcript antisense intergenic RNA (HOTAIR) is dysregulated in cancers and has emerged as a novel hotspot in the field. In breast cancer, aberrant HOTAIR expression is responsible for advanced tumor progression by regulating multifar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 125 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…The next cell line with the highest expression of HOTAIR is G401, an epithelial-like kidney cell derived from an infant rhabdoid tumor. It was reported that HOTAIR is highly expressed in atypical rhabdoid tumors ( 78 ). Overall, lncHUB2 prediction about HOTAIR’s biological functions are supported by literature, as well as producing predictions about additional HOTAIR’s roles in normal physiology and disease.…”
Section: Resultsmentioning
confidence: 99%
“…The next cell line with the highest expression of HOTAIR is G401, an epithelial-like kidney cell derived from an infant rhabdoid tumor. It was reported that HOTAIR is highly expressed in atypical rhabdoid tumors ( 78 ). Overall, lncHUB2 prediction about HOTAIR’s biological functions are supported by literature, as well as producing predictions about additional HOTAIR’s roles in normal physiology and disease.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor malignancy starts from transformation [ 1 , 2 , 3 ], apoptotic suppression [ 4 ] tumor proliferation [ 5 , 6 , 7 ], followed by tumor progression [ 2 , 8 , 9 , 10 ], epithelial–mesenchymal transition (EMT), and tumor/metastasis-initiating stemness [ 6 , 11 , 12 ], with which the tumor microenvironments of primary tumor tissues are closely cross-talked [ 8 ]. Primary tumor cells then enter the bloodstream to become circulating tumor cells (CTCs) and colonize into distant organs to form secondary metastatic tumor tissues [ 4 , 13 , 14 ] that lead to cancer death [ 15 ].…”
mentioning
confidence: 99%
“…Furthermore, dysregulated HOX transcript antisense intergenic RNA (HOTAIR) in breast cancer endogenously competes with several microRNAs and subsequently upregulates the levels of targeted downstream messenger RNAs, leading to aberrant signal transductions and further cancer progression. Shi et al have summarized current knowledge for the induction of HOTAIR in breast cancer and its impacts on cell proliferation, migration, apoptosis, therapeutic resistance, and the underlying mechanisms, providing new thoughts for anti-cancer therapeutic strategies against breast cancer [ 10 ]. During progression, the proliferation of tumor cells is promoted and apoptosis, including detached cell death anoikis, is suppressed.…”
mentioning
confidence: 99%